2017
DOI: 10.3892/mmr.2017.6831
|View full text |Cite
|
Sign up to set email alerts
|

Epoxyeicosatrienoic acid ameliorates cerebral ischemia-reperfusion injury by inhibiting inflammatory factors and pannexin-1

Abstract: Epoxyeicosatrienoic acid (EET) has wide applications due to the unique biological effects of anti‑hyperlipidemia, inhibition of platelet aggregation, anti‑inflammation, anti‑cancer, anti‑lipid oxidation and the promotion of brain tissue development. The present study investigated whether EET ameliorates cerebral ischemia‑reperfusion injury (CIRI) by inhibiting inflammatory factors and pannexin. Specific pathogen‑free 7‑week‑old male Sprague‑Dawley rats were randomly divided into three groups: Sham, CIRI and EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…CIRI can activate the NF-κB pathway and promote large-scale expression of various inflammatory factors (IFs), such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Studies also found that there are some important transcription factor binding sites in the IL-10 promoter region, such as those for NF-κB, c-Jun [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…CIRI can activate the NF-κB pathway and promote large-scale expression of various inflammatory factors (IFs), such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Studies also found that there are some important transcription factor binding sites in the IL-10 promoter region, such as those for NF-κB, c-Jun [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing EETs levels through genetic modi cation signi cantly increased the number of microvessels in liver and lung tissues [29]. EETs effectively ameliorate cerebral ischemia by increasing the microcirculation of brain tissue and improving the nutritional supply of brain nerves [30,31]. Our in vitro experiments indicated that TPPU enhanced the migration and tubule formation potentials of cocultured DPSCs and ECs.…”
Section: Discussionmentioning
confidence: 72%
“…The apoptosis marker cleaved caspase 3 (CC3) was employed in this study to evaluate the effect of RDA on BBB destruction during the progression of ischemia-reperfusion injury (Liu Z et al 2017;Liu C et al 2018). Immunoblotting data showed that an inactive mutant form of RIPK1 (Ripk1 D138N ) inhibited the initiation of RDA in mice after MCAO treatment; however, the RDA features remained intact in the Ripk3 −/− mice (Fig.…”
Section: Resultsmentioning
confidence: 99%